Pembelajaran Bahasa Arab Berbasis Al-Qur’an di Mushollah Zubhatul Hasan : Analisis Metode dan Penerapannya - Laili Ramadhani; Ainur Rofiq Sofa (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines the implementation of Arabic language learning based on the Qur'an at Mushollah Zubhatul Hasan, focusing on the sorogan and talaqqi methods. The sorogan method allows students to read directly in front of their teacher, receiving guidance on pronunciation, meaning, and sentence structure. This individual approach provides a more personalized learning experience, enabling students to receive immediate corrections. Meanwhile, the talaqqi method emphasizes listening and repeating the teacher’s recitation collectively, improving fluency, tajwid accuracy, and linguistic comprehension. Additionally, the practice of daily Arabic conversations in the Mushollah environment plays a crucial role in reinforcing language acquisition. Initially, students faced challenges in speaking Arabic, but continuous practice helped them develop confidence and fluency. This immersive approach allows students not only to learn Arabic theoretically but also to internalize it through practical use. The findings highlight that combining sorogan, talaqqi, and Arabic-speaking habits effectively enhances students’ Arabic proficiency, both in understanding Qur'anic texts and applying the language in daily interactions. This study underscores the importance of integrating structured teaching methods with real-life practice to achieve comprehensive Arabic language mastery in a religious learning setting.